(3ahGFO efJbGI ef GdLRA GdChd ef MOjK CHj eMeO YHO GdYRjR Hf GdMSf Hf Ydi Hf CHj UGHQ hef GdLRA GdChd ef MOjK CHj TYjH YHO Gddg Hf GdMSf Hf CMeO GdMQGfis - (3CHh eMeO GdMSf Hf Ydj Hf eMeO GdLhgQjs
(3ChdgG (B:s
(3CNHQfG GdTjN CHh eMeO YHO GdNGdb GdUGHhfi Yf CHj gQjQI bGd bGd QShd Gddg Udi Gddg Ydjg hSde (B: (3eKd GdPi jSeY GdMceI ajMOK HTQ eG jSeY GdMOjK s
(3BNQgG (B:s
(3Yf YGFTI bGdJ (B: (3cf GdfSGA jUdjf eY QShd Gddg UdGI GdaLQ eJdaYGJ HeQhWgf jQLYf Edi HjhJgf bHd Cf jYQaf , bGdJ (B: (3hcGf QShd Gddg Udi Gddg Ydjg hSde EPG Sde EfUQaf BNQg hGdMeO ddg hMOg s
(3GdfSNI HgG MhGTs
(3HBNQgG SeGYGJ cKjQI Ydi jhSa Hf Ndjd Hf YHO Gddg GdOeTbi hcJH HNWg UhQI GdSeGY SfI (B627 (3, (B628s
(3hYdi GdCUd Gdefbhd efg SeGYGJ cKjQIs
(3eUOQ GbJfGA GdCUd (B:s
(3GdecJHI GdeMehOjI (B- (3HecJHI GdeOjfI GdefhQI GdYGeI(B((3eLGejY (B154) s
Keywords: (3GdMOjK h GdeUWdMs